2019
DOI: 10.1016/j.cmet.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Application of Gene Expression Signatures Associated with Lifespan Extension

Abstract: Highlights d Sex-specific differences are decreased in response to longevity interventions d Many interventions, but not rapamycin, exhibit similar transcriptomic responses d Certain gene expression changes are associated with longevity across interventions d Longevity signatures may be used to discover new lifespanextending interventions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 151 publications
(237 reference statements)
9
146
0
Order By: Relevance
“…Enhanced bioavailability and/or production capacity of endogenous H2S, particularly via CGL activity, has only recently been recognized as a common phenomenon and proposed mechanisms of action for dietary, genetic, and pharmacological models of longevity and healthy aging across evolutionary boundaries Kabil et al, 2011a;Tyshkovskiy et al, 2019). However, the molecular mechanisms underlying many of the pleiotropic cellular, physiological, and systemic benefits of H2S, particularly and in the context of diet and aging, have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced bioavailability and/or production capacity of endogenous H2S, particularly via CGL activity, has only recently been recognized as a common phenomenon and proposed mechanisms of action for dietary, genetic, and pharmacological models of longevity and healthy aging across evolutionary boundaries Kabil et al, 2011a;Tyshkovskiy et al, 2019). However, the molecular mechanisms underlying many of the pleiotropic cellular, physiological, and systemic benefits of H2S, particularly and in the context of diet and aging, have remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of CGL expression and/or activity is attributed to hypertension (Yang et al, 2008), neurodegeneration (Paul et al, 2014), and the inability to properly respond to dietary and endocrine cues (Hine et al, 2015;Ishii et al, 2010;Kabil et al, 2011a;Longchamp et al, 2018;Nakano et al, 2015). Remarkably, it was recently found that increased CGL expression in liver is a hallmark of numerous dietary, genetic, hormonal, and pharmaceutical mouse models of extended lifespan and may serve as a molecular biomarker associated with longevity (Tyshkovskiy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple lifespan extending compounds, including 17α-E2, exhibit similar modifications in liver function [27]. In all, recent studies by several independent laboratories strongly indicate that the lifespanextending effects of 17α-E2 are at least associated with, if not dependent on, metabolic improvements.…”
Section: Introductionmentioning
confidence: 88%
“…We have found that 17α-E2 administration reduces food intake and regional adiposity in combination with significant improvements in a multitude of systemic metabolic parameters in both middle-aged obese and old male mice without inducing deleterious effects [22][23][24]. Other groups have also determined that lifelong administration of 17α-E2 beneficially modulates metabolic outcomes, including glucose tolerance, mTORC2 signaling, and hepatic amino acid composition and markers of urea cycling, which were reported to be dependent upon the presence of endogenous androgens [25,26].Additionally, multiple lifespan extending compounds, including 17α-E2, exhibit similar modifications in liver function [27]. In all, recent studies by several independent laboratories strongly indicate that the lifespanextending effects of 17α-E2 are at least associated with, if not dependent on, metabolic improvements.Despite the mounting evidence demonstrating that 17α-E2 improves numerous health parameters, the signaling mechanism(s) and primary tissues through which 17α-E2 elicits these benefits remain unknown.Although 17α-E2 is a naturally-occurring enantiomer to 17β-estradiol (17β-E2), it has been postulated that 17α-E2 signals through a novel uncharacterized receptor [28][29][30][31] as opposed to classical estrogen receptors alpha (ERα) and beta (ERβ); which is due to 17α-E2 having significantly reduced binding affinity to ERα and ERβ as compared to 17β-E2 [32][33][34][35].…”
mentioning
confidence: 99%
“…Older age is the greatest risk factor for the development of most chronic diseases (1). Accordingly, 98 recent large-scale 'omics' studies have aimed to characterize novel genes and biological pathways 99 that influence aging, and to identify related interventions (e.g., pharmaceutical compounds, exercise, 100 nutrition) that increase longevity and healthspan (2,3). Indeed, advances in transcriptomics (e.g., 101 RNA-seq) have led to important insight on many genes and pathways linked with 'the hallmarks of 102 aging' and broader health outcomes (4).…”
Section: Healthy Aging Interventions Reduce Non-coding Repetitive Elementioning
confidence: 99%